Pteris langsonensis (Pteridaceae), a new brake fern species from Lang Son Province, northern Vietnam - Zhang, Liang; Lu, Ngan Thi; Zhang, Li-Bing (Phytotaxa, 2015)
A new fern species, Pteris langsonensis belonging to the P. cadieri complex (Pteridaceae), is described and illustrated from Lang Son Province, northern Vietnam. P. langsonensis is most similar to P. plumbea, but the former has typical dimorphic leaves and fertile pinnae much contracted and with a width of no more than half of sterile pinnae, while the latter has slightly dimorphic leaves. The new species is also similar to P. cretica, but the former has smaller habit and slightly toothed sterile leaf margins.